WARNING DAN KONSEKWENSI HATE SPEECH DALAM AL-QURâ€™AN (Tafsir Tematik Ayat-Ayat â€œHate Speechâ€) - Amalia Isnaini; Amir Mahmud; Saifullah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
Hate speech becomes an unrest in society as a nation and state. This is due to concerns that hate speech could disrupt the harmony of society which has been running well. Hate speech seems to be increasingly finding an effective place to be carried out when social media is starting to be widely owned by people in Indonesia. In this way, hate speech becomes even more disturbing. This type of research is qualitative with data collection techniques using a library research approach. The data collection process was carried out by reading related literature, in the form of journals, books, articles and of course the Al-Qur'an as the main source in discussing hate speech and the hadith of the Prophet as a reinforcement of the Al-Qur'an. The results of this research indicate that hate speech has received strong criticism in the Al-Qur'an. In fact, the Al-Qur'an gives a cruel picture of people who tend to carry out hate speech and threaten painful torture. The consequences of hate speech are also mentioned a lot in the Al-Qur'an in the form of mentioning certain groups that were destroyed due to the violence (hate speech) carried out by their people.